Mentoring as a tool to engage Aboriginal youth in remote Australian communities: a qualitative investigation of community members, mentees, teachers, and mentors' perspectives. Issue 1 (1st January 2018) - Peralta, Louisa; Cinelli, Renata; Bennie, Andrew
Abstract: Sport-based mentoring programs have been used across many contexts to engage young people in education. In this research, we explored the influence that an Aboriginal controlled organisation's youth mentoring program has on three remote Aboriginal communities in Northern Territory, Australia. We used a composite set of culturally sensitive methods by including artefacts from the community members and mentees, informal interviews with community, and semi-structured conversations with mentors and schoolteachers. The findings demonstrate the positive feelings, many benefits, and relationships that had been established between mentors and mentees, the organisation and community over time. However, participants also suggested that it would be beneficial to engage mentors in activities with students not in the school system, and adults in the broader community. Despite some identified challenges, the mentoring program was perceived to be successful in engaging remote Aboriginal children in school and developing future career aspirations.